SHOT, a SHOX-related homeobox gene, is implicated in craniofacial, brain, heart, and limb development - Blaschke, Rüdiger J. (The National Academy of Sciences, 1998)
Deletion of the SHOX region on the human sex chromosomes has been shown to result in idiopathic short stature and proposed to play a role in the short stature associated with Turner syndrome. We have identified a human paired-related homeobox gene, SHOT, by virtue of its homology to the human SHOX and mouse OG-12 genes. Two different isoforms were isolated, SHOTa and SHOTb, which have identical homeodomains and share a C-terminal 14-amino acid residue motif characteristic for craniofacially expressed homeodomain proteins. Differences between SHOTa and b reside within the N termini and an alternatively spliced exon in the C termini. In situ hybridization of the mouse equivalent, OG-12, on sections from staged mouse embryos detected highly restricted transcripts in the developing sinus venosus (aorta), female genitalia, diencephalon, mes- and myelencephalon, nasal capsula, palate, eyelid, and in the limbs. SHOT was mapped to human chromosome 3q25-q26 and OG-12 within a syntenic region on chromosome 3. Based on the localization and expression pattern of its mouse homologue during embryonic development, SHOT represents a candidate for the Cornelia de Lange syndrome.